The Effect of Depression and Hopelessness on Suicidal Risk in Young People: The Mediating Role of Impulsivity - Anyerson Stiths Gómez-Tabares; Olber Eduardo Arango-Tobón; César Núñez; Gastón Adolfo Zapata Lesmes (Clinical Psychology in Europe)
[Background] Previous studies have documented that depression and hopelessness predict higher suicide risk in young people. However, the psychological mechanisms that may mediate these associations are unknown. The aim of this study was to analyze the effects of depression, hopelessness, and impulsivity on suicidal attempts and risk, and to explore the mediating role of impulsivity in these associations. [Method] A total of 1,645 young people participated with a mean age of 21.604 years (SD = 3.22) (68.8% female and 31.2% male). A sociodemographic form was applied to explore suicide attempts in the last year (SA), the Plutchik Suicide Risk (SR), Beck Hopelessness (BHS), Barratt Impulsivity (BIS), and Beck Depression Inventory (BDI) scales. Direct correlations were found among BHS, BDI, BIS, SA, and SR. [Results] The binary regression model showed that the variables BHS, BDI, and BIS explained between 33% and 49% of the variance of suicidal risk and 16% of the variance of suicide attempts. Structural equation analysis showed that impulsivity mediated the associations between depression, hopelessness, and suicidal risk, on the one hand, and mediated the associations between depression and suicide attempt, on the other hand, whose total direct and indirect effects were statistically significant. [Conclusion] The findings emphasize the importance of impulsivity as the mechanism influencing interactions between mood indicators and suicidal behavior in young populations.